PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNIN IN SCIENCE (CLIS) TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP MUHAMMADIYAH 1 MEDAN - Shinta Dewi Safira; Inayah Hanum (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
The problems found in the study were the lack of motivation and knowledge of students in learning to write explanatory texts, students having difficulty in expressing or developing ideas on the use of linguistic structures and rules, and students being bored and bored in learning because teachers rarely use learning models that involve students directly. active in learning to write explanatory text. This study aims to determine the effect of using the Children Learning In Science (CLIS) learning model on the ability to write explanatory texts in class VIII students of SMP Muhammadiyah 1 Medan in the academic year 2022/2023. The method used in this study is the experimental method of the two group post-test design. From the data processing, the results obtained from the experimental group with an average value = 83, 75 ; standard deviation = 7,03 ; standard error = 1,20 ; and classified as very good category. While the results of the control group with an average value = 62,67 ; standard deviation = 10,29 ; standard error = 1,76 ; and classified as sufficient category. Based on the results of the analysis, it was found that the results of the data were normally distributed. Furthermore, the results of the homogeneity test analysis obtained that the sample came from a homogeneous variant. In testing the t-test hypothesis, the value of tcount is 9,94; and ttable with a significance level of ? = 0,05 with dk n-1=35-1=34 obtained ttable which is 1,691. This proves that the value of tcount (9,94) ttable (1,691), so that Ho is rejected, by rejecting Ho then Ha is accepted. So, it can be concluded that there is a significant influence between the use of the Children Learning In Science (CLIS) learning model on the ability to write explanatory texts in class VIII students of SMP Muhammadiyah 1 Medan in the academic year 2022/2023. Keywords: Influence, Children Learning In Science (CLIS), Explanatory Text.